Adverse events of emergency surgical front of neck airway access: an observational descriptive study. Issue 1 (15th April 2022) - Okada, Asami; Okada, Yohei; Kandori, Kenji; Ishii, Wataru; Narumiya, Hiromichi; Iizuka, Ryoji
Abstract : Aim: Emergency front of neck access (eFONA), such as scalpel cricothyroidotomy, is a rescue technique used to open the airway during "cannot intubate, cannot oxygenate" situations. However, little is known about the adverse events associated with the procedure. This study aimed to describe the adverse events that occur in patients who undergo eFONA and their management. Methods: This retrospective observational cohort study included emergency patients who underwent eFONA between April 2012 and August 2020. We described the patients' characteristics and the adverse events during or immediately after the procedure. Results: Among 75, 529 emergency patients during the study period, 31 (0.04%) underwent an eFONA. The median (interquartile range) age was 53 (39–67) years, and 23 patients (74.2%) were men. Of all cases, 13 (41.9%) experienced adverse events. Of these, three cases (23.2%) were cephalad misplacement of the intubation tube, one case (7.7%) was cuff injury, one case (7.7%) was tube obstruction due to vomiting, and one case (7.7%) was tube kink. In cases with these adverse events, the initial attempt of eFONA failed, and alternative immediate action was necessary to secure the airway. Conclusion: This single‐center retrospective observational study described several adverse events of eFONA. In particular, it is important to understand the possible life‐threatening adverse events that lead to failure of securing airways such as cephalad displacement, tube obstruction, and tube kink and respond promptly to ensure a secure definitive airway for patients' safety. Abstract : This retrospective observational study reported adverse events of an eFONA, including one lung intubation, cephalad misplacement of the intubation tube, and hemorrhage. It is important to understand the possible adverse events due to eFONA and respond promptly to ensure a secure definitive airway for patients' safety.